The Influence of Self-Efficacy Beliefs of University English Instructors on their Pedagogy - Zahir Hasan (Indonesian Journal of EFL and Linguistics, 2022)
This research study examines teaching beliefs of English-language instructors in Japan, and how their pedagogy is influenced by those beliefs.  An Interpretative Phenomenological Analysis (IPA) research design was used.  Seven English-language instructors employed full-time in universities in Tokyo prefecture of Japan participated in this study.  Social Cognitive Theory was used as the theoretical framework.  It was observed that each instructor’s beliefs interacted in a complex manner within the higher education system in Japan, which impacted instructors’ teaching practices.  This study demonstrated that language instructors’ self-efficacy (LTSE) beliefs are intrinsically related to their pedagogy.  It revealed a complex relationship between what instructors think and what they may do in class.  Findings of this study suggest that English Language instructors’ beliefs are key to their decision-making. In addition, the findings will provide valuable implications for ways to better understand the impact that personal beliefs of instructors have on curriculum and learning.  Finally, it has implications for professional education programs for teachers and brings attention to potential research directions for scholars.